IDENTIFIKASI FAKTOR-FAKTOR MANAJEMEN PEMELIHARAAN DAN IMPLEMENTASINYA PADA RUMAH SUSUN DI DKI JAKARTA - Eko Priyo Prastyo; Andreas Franskie Van Roy (TATALOKA, 2019)
Flats are concrete form of government policies in the provision of residence in urban area. In their operation, flats are required to be managed and maintained. Such treatment are required in order to achieve a goal which was defined in the Constitution of the Republic of Indonesia 1945 and Act No. 4 of 1992 that every citizen has right to have prosperous life physically and mentally by having habitable house in good environment, healthy, safe, comfortable, affordable, and productive. However, according to some studies technical and non-technical problems were found. Technical problems are connected to the building function. These problems cannot be separated from administration problems of flat maintenance management system. Being aware that flat maintenance management system is a complex system, this paper intends to identify the factors which include into different aspects as well as investigate how far those factors implemented. Based on identification, 22 factors of maintenance management system organization were generated and they were divided into five aspects. Survey which is done on eight flats that is managed by each PPPSRS in Special Capital Region of Jakarta finds that not all factors are done. Three PPPSRS do less than one third of those identified factors. The rest of them, five PPPSRS do more than two third of those factors. Based on survey and analysis found that capacity building enhancement is a must for PPPSRS in order to improve factor implementation level.